Nutrient Content and Dry Matter Degradability of Acacia Species in Arid and Semi-Arid Land of Baringo County, Kenya - Kandie, H. C.; Kitilit, J. K.; Oliech, G. W. O.; Ondiek, J. O. (Africa Environmental Review Journal, 2020)
The inadequate grass-based feed sources in arid and semi-arid lands (ASALs) constraint livestock production. Acacia trees and shrubs form the dominant vegetation in parts of the ASAL of Sub-Saharan Africa where they offer solutions to feed shortage. The current study examined the nutrient content and dry matter degradability of Acacia species preferred by goats in Marigat Sub- County, Baringo County. The collected samples of Acacia spp. leaves were cleaned with water, air-dried in the shade for five days, thoroughly mixed and ovendried at 60oC for 24 hrs, then grounded and packed in air-tight polythene bags. The samples were analysed for proximate composition before 200 mg of the sample was subjected to invitro degradability. The data obtained was subjected to ANOVA. The dry matter (DM) for all the tree species ranged from 95.42% in A. mellifera to 97.21% in A. nilotica leaves and was not significantly different. The crude protein (CP) content was significantly high in A. Mellifera at 22.00% while the fibre content was significantly different with A. brevispica at 28.12%. The ash content was significantly high in A. senegal at 15.59%. The findings of invitro dry matter degradation (IVDMD) indicated that A. nilotica had highest gas production at 48 hours followed by A. senegal at 24 hours. The gas production at 48 hours for A. nilotica leaves was significantly different (p<0.05) from A. brevispica leaves. The study concludes that A. nilotica was highly degradable followed by A. tortilis with least degradable being A. brevispica. The study recommends A. tortilis and A. brevispica, be used as supplements for livestock feeds in the ASAL regions, and thereby alleviate nutrient scarcities and reduce livestock malnutrition. A. brevispica provides fodder continuously to the pastoralist and therefore it can be propagated as a climate mitigation measure and as an alternate feed for the livestock during droughts.